The Impact of Health Spending, Education Spending and Economic Growth on Human Development: A Provincial Panel Analysis - Sijabat, Rosdiana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the impact of health spending, education spending, and regional economic growth on human development in 34 provinces across Indonesia from 2012-2020. The panel data regression method examined the association between the studied variables. The random effect model demonstrated a positive and significant impact of education spending and regional economic growth on human development in 34 provinces. Meanwhile, inconsistent economic growth findings negatively and significantly affect human development. By contrast, health spending is not significantly associated with subsequent HDI in the model estimated. The study's results imply that government spending on education was the most profitable investment in human resource development in the period under review.